2014
DOI: 10.1016/j.ydbio.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific repression of dachshund is required for Drosophila sex comb development

Abstract: The origin of new morphological structures requires the establishment of new genetic regulatory circuits to control their development, from initial specification to terminal differentiation. The upstream regulatory genes are usually the first to be identified, while the mechanisms that translate novel regulatory information into phenotypic diversity often remain obscure. In particular, elaborate sex-specific structures that have evolved in many animal lineages are inevitably controlled by sex-determining genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Specifically, dsx controls sex-specific trait growth by binding cis-regulatory regions of downstream target genes (114,162,192). Both general and tissue-specific expression modifications of dsx can contribute to sexual dimorphism in trait size (90,109,153,168) by controlling downstream patterning genes responsible for trait development, as observed for primary sexual traits such as genital structures and gonads (5,24,87,153) and secondary traits such as the male-specific sex combs of some Drosophila flies (6,168).…”
Section: Sexually Dimorphic Exaggerated Traitsmentioning
confidence: 99%
“…Specifically, dsx controls sex-specific trait growth by binding cis-regulatory regions of downstream target genes (114,162,192). Both general and tissue-specific expression modifications of dsx can contribute to sexual dimorphism in trait size (90,109,153,168) by controlling downstream patterning genes responsible for trait development, as observed for primary sexual traits such as genital structures and gonads (5,24,87,153) and secondary traits such as the male-specific sex combs of some Drosophila flies (6,168).…”
Section: Sexually Dimorphic Exaggerated Traitsmentioning
confidence: 99%
“…6), in the wing blade, ectopic Dac might limit ban expression by restricting the activity of the Yki-Mad or Yki-Sd complexes on additional enhancers. In addition, Dac appears to regulate the expression of distinct sets of patterning genes depending of the cellular context, as dac is also required for establishing the segmental pattern of Notch ligand and fringe expression in the leg imaginal disc, for sensory organ, genitalia and sex comb development and for proper neuronal differentiation (Atallah et al, 2014;Keisman and Baker, 2001;Martini et al, 2000;Miguel-Aliaga et al, 2004;Okamoto et al, 2012;Rauskolb, 2001). …”
Section: Dac Is An Inhibitor Of Yki-hth Transcriptional Activitymentioning
confidence: 99%
“…Several genes are known to affect the specification and development of the sex comb, such as Scr (Lewis et al , 1980a, b; Barmina and Kopp, 2007; Tanaka et al , 2011), dac (Atallah et al , 2014), the sex determination pathway genes dsx and transformer 2 , tra2 (Baker and Ridge, 1980; Tanaka et al , 2011) and a series of genes named based on their effect on the sex comb ( Additional sex combs , extra sex combs , multi sex combs , Posterior sex combs , Sex comb on midleg , Sex combs extra and super sex combs ). Although some of these genes, such as dsx and Scr (Graze et al , 2007), have been implicated within QTL intervals identified in previous mapping studies, none of them are present within the three QTLs we map in the DSPR (Supplementary File S7).…”
Section: Resultsmentioning
confidence: 99%
“…None of the three QTLs we map implicate dac , dsx , Scr or tra2 (Supplementary File S7), the four genes that have been shown to be involved in the specification and development of the sex comb (Baker and Ridge, 1980; Lewis et al , 1980a, b; Barmina and Kopp, 2007; Tanaka et al , 2011; Atallah et al , 2014). Although not formally significant at a 5% permutation-derived threshold (Churchill and Doerge, 1994), we observed three additional peaks in the LOD (logarithm (base 10) of odds) score profile that are close to genome-wide significance (X, 0.5 cM; 2L, 54.0 cM; and 2R, 87.5 cM; Figure 2 and Supplementary File S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation